2021
DOI: 10.1002/bse.2756
|View full text |Cite
|
Sign up to set email alerts
|

Green aviation industry sustainable development towards an integrated support system

Abstract: Sustainable development is becoming increasingly crucial for the green aviation industry. To promote the sustainable development of the green aviation industry, researchers all over the world have attempted to explore and experiment with new initiatives. This study investigates green aviation industry development trends by a bibliometric-based data analysis system. Cluster, timezone, and timeline visualizations are employed to identify the current development trends of the green aviation industry within three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Remarkably, various studies have found that many firms have received environmental awards and faced significant losses, indicating that market partners are not considering the environmental aspects in their investment decisions (Huynh 2020 ; Qiu et al 2021 ). Consistent with the outcomes of Giuli and Kostovetsky (2012) study when they reported that the environment-protected projects represent an extra cost on the firm and are negatively related to the market and financial performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Remarkably, various studies have found that many firms have received environmental awards and faced significant losses, indicating that market partners are not considering the environmental aspects in their investment decisions (Huynh 2020 ; Qiu et al 2021 ). Consistent with the outcomes of Giuli and Kostovetsky (2012) study when they reported that the environment-protected projects represent an extra cost on the firm and are negatively related to the market and financial performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The aviation sector has well‐known and significant detrimental effects on the environment (Hinnen et al, 2017; Qiu et al, 2021; Vespermann & Wittmer, 2011). These include problems of high visibility and concern (Hinnen et al, 2017; Lopes de Sousa Jabbour et al, 2020), such as aircraft noise, local air contamination, water utilisation and pollution and special impacts on climate change through carbon emissions (Daley & Thomas, 2011; Payán‐Sánchez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One problem is that certain advances in technology may undermine the pursuit of long-term, sustainable development efforts (Cao et al, 2021). While the use of new and emerging technologies may accelerate progress toward sustainability, it can also disrupt markets and economies, aggravate social divisions, and pose moral issues (Qiu et al, 2021). Because the field of sustainability research is still not properly defined, developed, or applied, many businesses in developing economies today lack the knowledge needed to successfully adopt and adapt sustainable strategies (Luthra et al, 2017).…”
Section: Covid-19 and Emerging Technology For Sustainabilitymentioning
confidence: 99%